Postponing the legal retirement age - Juan A. Lacomba; Francisco Lagos (SERIEs - Journal of the Spanish Economic Association, 2010)
This paper analyzes the reform of the pensionable age as an answer to the future financing problems of public pension systems. We use a two-staged model where, first, the government decides the redistribution level of the pension system and, secondly, individuals face a voting process on the legal retirement age. The results suggest that governments attempting to postpone the legal retirement age should increase the degree of intra-generational redistribution of the pension system in order to make the reform aimed at more easily achievable. More importantly, the most productive individuals could support some degree of redistribution to that aim.
Keywords: H55; J26; 330; legal retirement age; voting process; degree of redistribution; Flexible Altersgrenze; Rentenreform; Rentenfinanzierung; Verteilungswirkung; Wirtschaftswissenschaft; Theorie